2006
DOI: 10.1039/b607066c
|View full text |Cite
|
Sign up to set email alerts
|

Dissolvable membranes as sensing elements for microfluidics based biological/chemical sensors

Abstract: We demonstrate a chemical and biological sensing mechanism in microfluidics that transduces chemical and biological signals to electrical signals with large intrinsic amplification without need for complex electronics. The sensing mechanism involves a dissolvable membrane separating a liquid sample chamber from an interdigitated electrode. Dissolution of the membrane (here, a disulfide cross-linked poly(acrylamide) hydrogel) in the presence of a specific target (here, a reducing agent-dithiothreitol) allows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…With the use of PVA as a time barrier film, the sample will not flow until the required time. This allows increased exposure time between protein and antibody in order to allow more immuno-complexes to be formed in order to ensure higher sensitivity, reactivity, and reduced false-positive signal [1,2,5]. In addition, as previously discussed, the PVA solubility depends on its molecular weight and degree of hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of PVA as a time barrier film, the sample will not flow until the required time. This allows increased exposure time between protein and antibody in order to allow more immuno-complexes to be formed in order to ensure higher sensitivity, reactivity, and reduced false-positive signal [1,2,5]. In addition, as previously discussed, the PVA solubility depends on its molecular weight and degree of hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of the sample, the membrane dissolves and permits the sample flow into interdigitated electrodes. This results in a resistance change between the electrodes and transduces the chemical event into an electrical signal [5]. However, in order for such dissolvable membranes to be employed in high-speed sensing technologies, the total operation time of the device should be approximately 30 min or less.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acoustofluidic waveguides with cross-sectional shapes other than circle, square, and triangle could also be exploited for the localized shaping of the acoustic fields in microfluidics. Our studies revealed that some of these structures are capable of yielding quite unique field profiles, which are extremely sensitive to the geometric modifications and/or the frequency changes, making themselves appealing platforms for some specific biomedical applications (Lee et al 2014; Liu et al 2012; Sridharamurthy et al 2006). Furthermore, through designing more complex structures (e.g., waveguide arrays) and introducing novel configurations like acoustic metasurfaces (Li et al 2013, 2014b; Xie et al 2014) and/or phononic crystals (Bourquin et al 2011; Lin et al 2009), we envision the exploitation of our acoustofluidic waveguide platform in realizing even more complex and integrated functionalities.…”
Section: Discussionmentioning
confidence: 94%
“…The porous membrane, interfacially formed in situ , will enable relatively easy fabrication of microfluidic filtration devices. The porous membrane may also be applicable to biological applications, such as cell migration and invasion devices19 and detection devices 30, 31. However, further study should be done to investigate the biocompatibility of the porous membrane.…”
Section: Discussionmentioning
confidence: 99%